The Spectrum of Biopsy-Proved Kidney Disease: A Retrospective Single Center Study in Erbil-Iraq - Al-Imam, Ahmed; Ali, Mudhafar Abdullah; Al-Mukhtar, Safa Ezzaddin (Asian Journal of Medical Sciences, 2019)
BACKGROUND Renal biopsy is crucial to determine the pattern of the different types of renal diseases. It represents the gold standard of diagnostics for renal pathologies, including glomerular diseases, and it has an important value for the prognosis, monitoring disease progression, and planning the management protocol. AIMS AND OBJECTIVE To report the frequency of different pathological lesions affecting the kidney in patients who were admitted to our medical centre. MATERIALS AND METHODS This is a retrospective study of all patients with renal diseases who underwent percutaneous renal biopsy at the Erbil Kidney Centre for eight years (1st of January 2010 to 31st of December 2017). A total of 893 cases were biopsied and subsequently studied via histopathological examination and immunofluorescence microscopy. The study is ethically permitted by the Kurdistan Board for Medical Specialization. RESULTS The average age of the patients was 30.9 years. The most common clinical indication for biopsy included nephrotic syndrome (46.47%), acute renal failure (19.04%), chronic renal failure (15.34%), nephritic syndrome (7.39%), proteinuria alone (7.28%), and hematuria alone (4.48%). In patients with a primary glomerular disease, focal segmental glomerulosclerosis and minimal change disease were the most frequent (27.44% and 16.01%) in the younger patients (18.61±13.47 years), while membranous glomerulonephritis was more common in older patients (38.94±13.69 years). Patients with a secondary glomerular disease were mainly diagnosed with lupus nephritis, amyloidosis, and diabetic nephropathy. CONCLUSION The epitome of our study signifies that the spectrum of glomerular diseases varies based on age, sex, ethnicity, and geographical distribution. The implementation of renal biopsy proved to be a cornerstone in reaching the correct diagnosis. Future studies should implement the use of electron microscopy in conjunction with classical techniques of histopathology and immunofluorescence microscopy to diagnose equivocal cases of interest.